"Against the Cult of Things": On Soviet Productivism, Storage Economy, and Commodities with No Destination. Issue 2 (April 2014) - OUSHAKINE, SERGUEI ALEX.
<x xml:space="preserve">Abstract</x> Following an emerging trend in the ethnography of socialist things, this article seeks to move beyond the powerful paradigms of "the culture of shortage" and "the economy of scarcity" that have been defining the studies of socialist consumption for the last few decades. By displacing "scarcity" as the primary explanatory lens on Soviet consumption, we can open up some analytical and ethnographic room for processes, practices, concepts, or paradigms that have been overshadowed by the politically charged emphasis on shortages. The dominant Soviet perception of consumption as a form of production reduced the complexity of the Soviet commodity to one dimension: use‐value. In the situation of a planned economy with regulated prices, neither exchange‐value, nor even value itself, were of particular importance or interest for those who determined the shape and structure of Soviet consumption. The Soviet commodity made itself known through its "sensuous characteristics" and its ability to meet (or, more commonly, fail to meet) the requirements of functionality. When seen in this context, the productivist framework of Soviet‐style consumption emerges less as a material representation of "the dictatorship over needs"–with "the perfect homogenization of society and the (perhaps forcible) uniformization of needs" as its main goal–but rather as a historically situated attempt to take rationality (and rationalization) to its limits.